Understanding the Material Impact of Social Media during Public Criticism and Dissent in African Countries: A Review of the Literature - Mabinane, Letjedi Thabang (International Journal of Mass Communication, 2024)
Globally, governments are imposing national blackouts on digital communication, particularly the internet and subsequently the social media space during public criticism and dissent. To understand the material impact of this digital blackout, a literature review is conducted, focusing on African countries. The objective of this study was to examine the impact of social media during public criticism and dissent from an African perspective. To achieve this, an extensive review of the literature was conducted on African countries. The United Nations (UN) classifies 54 countries as African. All these countries had a known chance of being selected as part of the sample (probability sampling). In total, 29 countries were chosen based on relevance and the availability of data on internet shutdowns. Furthermore, the study looks into a 5-year trend from 2018 to 2022. Consequently, the results suggest that internet shutdowns in Africa are currently on the rise and remain disruptive, oppressive, expensive, and cost countries dearly. Additionally, the study also found that internet shutdowns often result in violent and/or fatal protests. It was further found that the responses by governments and companies during public criticism and dissent have been challenging, insufficient, and detrimental to human rights. At a country level, Ethiopia, Sudan, and Chad - respectively remain the regional leaders in terms of shutting down the Internet. This research recommends more scientific research to be conducted under the topic to enrich the existing body of knowledge, and possibly refine the findings of the current study. It further recommends country-specific policies that should openly condemn government-imposed internet shutdowns. Moreover, this research also recommends that global Human Rights Organisations should stand firm and strongly condemn government-imposed internet shutdowns by imposing sanctions and repercussions for oppressive governments. Finally, this research concludes that social media has unique capabilities to convey messages to larger groups of people, mobilizing or immobilizing them with only a few clicks. Among others, social media can also spread fake information or news by posting old material and linking it to current situations.